A descriptive study of the perceptions and motivations of consumers on how to successfully implement a tax lottery in South Africa to improve tax compliance behaviour - Schoeman, Anculien (University of Pretoria, 2023)
Mini Dissertation (MCom (Taxation))--University of Pretoria, 2022.